Resveratrol inhibits NLRP3 inflammasome activation by preserving mitochondrial integrity and augmenting autophagy. Issue 7 (July 2015) - Chang, Ya‐Ping; Ka, Shuk‐Man; Hsu, Wan‐Han; Chen, Ann; Chao, Louis Kuoping; Lin, Chai‐Ching; Hsieh, Cho‐Chen; Chen, Ming‐Cheng; Chiu, Huan‐Wen; Ho, Chen‐Lung; Chiu, Yi‐Chich; Liu, May‐Lan; et al.
Abstract : The NLRP3 inflammasome is a caspase‐1‐containing multi‐protein complex that controls the release of IL‐1β and plays important roles in the development of inflammatory disease. Here, we report that resveratrol, a polyphenolic compound naturally produced by plants, inhibits NLRP3 inflammasome‐derived IL‐1β secretion and pyroptosis in macrophages. Resveratrol inhibits the activation step of the NLRP3 inflammasome by suppressing mitochondrial damage. Resveratrol also induces autophagy by activating p38, and macrophages treated with an autophagy inhibitor are resistant to the suppressive effects of resveratrol. In addition, resveratrol administration mitigates glomerular proliferation, glomerular sclerosis, and glomerular inflammation in a mouse model of progressive IgA nephropathy. These findings were associated with decreased renal mononuclear leukocyte infiltration, reduced renal superoxide anion levels, and inhibited renal NLRP3 inflammasome activation. Our data indicate that resveratrol suppresses NLRP3 inflammasome activation by preserving mitochondrial integrity and by augmenting autophagy. J. Cell. Physiol. 230: 1567–1579, 2015. © 2014 Wiley Periodicals, Inc., A Wiley Company